1997
DOI: 10.1038/bjc.1997.189
|View full text |Cite
|
Sign up to set email alerts
|

Histamine-stimulated expression of insulin-like growth factors in human glioma cells

Abstract: Summary Glioma tumour growth is associated with the expression of insulin-like growth factors and 11 (IGFs) and of both type and type 11 IGF receptors. It has also been shown that IGFs can stimulate proliferation of cultured glioma cells. We previously reported that histamine too can stimulate the growth of glioma cells in vitro. In this report, we study whether the histamine-induced growth of G47 glioma cells is mediated by the IGFs. We found that histamine stimulates the expression of both IGF-I and IGF-11 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0
1

Year Published

1999
1999
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 46 publications
(47 reference statements)
1
4
0
1
Order By: Relevance
“…This suggested that the histamine pathway may undertake crosstalk with the IGF‐1R/PI3K/AKT signalling pathway. This is consistent with other reports showing that histamine increased the growth of glioma cells by inducing the expression of IGF‐1, and blocking the proliferation‐inducing effect of supplemented IGF‐I did not affect histamine‐stimulated proliferation . We found that the PI3K antagonist blocked the histamine proliferative effect on C2C12 cells, and the histamine H3 receptor antagonist blocked the histamine effect on C2C12 cell proliferation.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This suggested that the histamine pathway may undertake crosstalk with the IGF‐1R/PI3K/AKT signalling pathway. This is consistent with other reports showing that histamine increased the growth of glioma cells by inducing the expression of IGF‐1, and blocking the proliferation‐inducing effect of supplemented IGF‐I did not affect histamine‐stimulated proliferation . We found that the PI3K antagonist blocked the histamine proliferative effect on C2C12 cells, and the histamine H3 receptor antagonist blocked the histamine effect on C2C12 cell proliferation.…”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with other reports showing that histamine increased the growth of glioma cells by inducing the expression of IGF-1, and blocking the proliferation-inducing effect of supplemented IGF-I did not affect histamine-stimulated proliferation. 23 We found that the PI3K antagonist blocked the histamine proliferative effect on C2C12 cells, and the histamine H3 receptor antagonist blocked the histamine effect on C2C12 cell proliferation. These results suggest that histamine promotes C2C12 cell proliferation by activating PI3K/AKT via the H3 receptor (H3R).…”
Section: This Is Consistent With Previous Studies Showing That Mice Lmentioning
confidence: 60%
See 2 more Smart Citations
“…However, with intracrine signaling, stimulation occurs before the growth factor can be released to the extracellular environment via interaction with intracellular receptors (Re 2002). In recent years, there has been a growing interest in intracrine signaling, particularly with regard to the endothelial growth factor (EGF) (Wiley et al 1998), FGF (Bilak et al 2003;Stachowiak et al 1997), angiotensin II (Baker et al 2004) and IGF (Dubois et al 1993;Lin et al 1997;Van der Ven et al 1997;Baumrucker 2005) families. In our studies, addition of exogenous growth factors or other effectors, such as IGFBP-3, failed to alter the barrier properties of parental cells; likewise, addition of IGFBP-3 in order to bind endogenously secreted IGF-I did not impact the IGF-I-secreting cell line barrier properties.…”
Section: Discussionmentioning
confidence: 99%